The Implementation Of Class Agreements In Strengthening The Discipline Of Elementary School Students - Margaretha Loyz Armelita Florentia; Nur Joan Adiwinata; Seviena Muria Putri; Rawanoko, Endrise Septina (CAKRAWALA: Journal of Citizenship Teaching and Learning, 2024)
This study discusses the implementation of classroom agreements in strengthening the discipline of elementary school students. Classroom agreements serve as a tool to create a conducive learning environment, where students feel valued and responsible for their behavior. Through active student participation in the creation of agreements, they not only learn about discipline but also important social values. The research shows that consistent application of classroom agreements, accompanied by consequences and rewards, can significantly enhance student discipline. The findings indicate that students involved in the rule-making process are more likely to adhere to the agreed-upon agreements. Thus, classroom agreements become an effective strategy in shaping the disciplined character of elementary school students.